Influence of alloying elements and the state of order on the formation of antiphase boundaries in B2 phases. (February 2022) - Vidal, Daniel; Hillel, Guy; Edry, Itzhak; Pinkas, Malki; Fuks, David; Meshi, Louisa
Abstract: Alloys with single phase B2 structure exhibit interesting physical properties, such as stability at high temperatures and oxidation resistance, but have low fracture toughness and limited ductility. The presence of antiphase boundaries (APBs) has been proposed as one of the factors improving the ductility of the B2 phases. An example of novel B2/A2 dual-phase alloy, which comprises such defects, is the AlCoCrFeNi multicomponent alloy (also known as high-entropy alloy (HEA)). Presence of APBs positively affected the performance of this alloy; therefore, control over the appearance of APBs is important. Current paper presents a first step in this direction, by studying the energy of APBs formation in binary B2 structures forming in the Al–Co–Cr–Fe–Ni system as a function of doping by ternary element from this system. Calculations, based on Density Functional Theory, took into account atom occupancy of the additives ( i.e . in Al or in transition metal's sub-lattice) and position (at the APBs or at grains' interior). Following the presented here calculations, casting and characterization of the alloy, where APBs should be promoted, was made, proving the outcomes of this work. AlFe binary system was found to be the most probable (out of all possible binary prototypes) to form APBs. Furthermore, alloying by Cr (which substitutes Al) and Ni (which substitutes Fe) promote even more APBs formation. Taking into account anti-site defects, frequently forming in the AlFe B2 structure, the degree of disorder was related to the temperature – proposing an interesting aspect of promoting the formation of APBs. Highlights: AlFe binary system was found to be the most probable to form APBs. In both AlNi and AlFe - alloying by Cr and Ni promote APBs. Addition of Co raises the APBs formation energy. In AlFe, addition of any atom is preferable inside the grains. CoAl it is almost improbable to form APBs, since energy is extremely high.